(untitled) - Brady, James E. (New York, 1990)
The book is divided into six parts. Part I presents a basic introduction to chemical concepts and the development of stoichiometric principles. Part II centers on the development of theoretical explanations of observed facts. Part III focuses on the physical properties of substances. It deals with the states of matter and intermolecular attractions as well as the physical properties mixtures. In Part IV the spotlight is on factors that determine the outcome of chemical reactions. Part V surveys the chemistry of the elements. Finally, Part VI concludes the text with a discussion of nuclear reactions and their role in chemistry.
Keywords: Chemistry